Pest risk assessment of Amyelois transitella for the European Union. (8th November 2022) - ,; Bragard, Claude; Baptista, Paula; Chatzivassiliou, Elisavet; Di Serio, Francesco; Gonthier, Paolo; Jaques Miret, Josep Anton; Justesen, Annemarie Fejer; MacLeod, Alan; Magnusson, Christer Sven; Milonas, Panagiotis; Navas‐Cortes, Juan A; et al.
Abstract: Following a request from the European Commission, the EFSA Panel on Plant Health performed a pest risk assessment of Amyelois transitella (Lepidoptera: Pyralidae), the navel orangeworm, for the EU. The quantitative assessment considered two scenarios: (i) current practices and (ii) a requirement for chilled transport. The assessment focused on pathways of introduction, climatic conditions and cultivation of hosts allowing establishment, spread and impact. A. transitella is a common pest of almonds, pistachios and walnuts in California, which is the main source for these nuts imported into the EU. Based on size of the trade and infestation at origin, importation of walnuts and almonds from the USA was identified as the most important pathways for entry of A. transitella. Using expert knowledge elicitation (EKE) and pathway modelling, a median estimate of 2, 630 infested nuts is expected to enter the EU each year over the next 5 years (90% certainty range (CR) from 338 to 26, 000 infested nuts per year). However, due to estimated small likelihoods of transfer to a host, mating upon transfer and survival of founder populations, the number of populations that establish was estimated to be 0.000698 year −1 (median, 90% CR: 0.0000126–0.0364 year −1 ). Accordingly, the expected period between founding events is 1, 430 years (median, 90% CR: 27.5–79, 400 year). The likelihood of entry resulting in establishment is therefore considered very small. However, this estimate has high uncertainty, mainly concerning the processes of transfer of the insect to hosts and the establishment of founder populations by those that successfully transfer. Climate matching and CLIMEX modelling indicate that conditions are most suitable for establishment in the southern EU, especially around the Mediterranean basin. The median rate of natural spread was estimated to be 5.6 km/year (median, 90% CR 0.8–19.3 km/year), after an initial lag period of 3.1 year (mean, 90% CR 1.7–6.2 year) following the establishment of a founder population. If A. transitella did establish, estimated median yield losses in nuts were estimated to be in the order of 1–2% depending on the nut species and production system. A scenario requiring imports of nuts to be transported under chilled conditions was shown to provide potential to further reduce the likelihood of entry.